What should be the primary end point in irritable bowel syndrome?. (February 2013) - Mangel, Allen W
Irritable bowel syndrome, one of the most common gastrointestinal disorders, is characterized by abdominal pain/discomfort and disturbances in bowel functions. Choosing the correct primary end point in irritable bowel syndrome clinical trials has a profound impact on whether a novel therapeutic may be advanced to the next stage of clinical development. During the past decade, both the US FDA and the European Medicines Agency have issued guidance documents recommending primary end points for irritable bowel syndrome studies. Currently these guidance documents are not harmonized, and some of the recommended end points have not gone through a validation process. The current perspective provides the author's recommendation for what should be the primary end point in irritable bowel syndrome clinical trials.